Investigation of the thermal field in micro friction surfacing - Vitanov, V. I.; Javaid, N. (Elsevier, 2010)
To model the thermal response of the micro friction surfacing process with complex geometries and to tackle transient deposition processes, suitable numerical methods have been developed. The approach of coupled transient thermal analysis to account for the temperature fields generated during the dwell and deposition phases of the process resulted in reasonably accurate results, with an error of 18% between absolute maximums. The major discrepancy between the experimental and simulated results occurred at locations with a change in substrate geometry. The heat distribution profile at the frictional interface and variation in material properties with temperature could have significant effects on the thermal response.
Keywords: Coating; Thermal modeling; Friction surfacing